Blockchain Technology in the Future of Enterprise Security System from Cybercrime - Maesaroh, Siti; Permana, Handy Januar; Dirgayusa Febrianaga, Pipit; Noviyanti; Pardosi, Renhad Andreas (Blockchain Frontier Technology, 2022)
This study looks into the current, and potential uses of Blockchain technology in business, specifically in security system of enterprise. The goal of this study is to use modern blockchain technology to address the problem of enhancing the degree of cybersecurity in huge corporations. Enterprises that have seen examples of cyber fraud perpetrated not only by hackers but also by business personnel have evaluated the urgency of the matter. The authors have developed a blockchain-based system dynamic model of the company's cybersecurity system. The use of this modeling tool enables the creation of a computer model of a complicated cybersecurity system, which can then be used to design the suggested update more effectively. We show how Blockchain affects auditing in a variety of ways that will fundamentally alter the profession. We also believe that blockchain technology should be integrated into other parts of cybersecurity, including auditing and general accounting operations. The findings have allowed researchers to draw conclusions about the increased system response in cases of employee fraud in the context of a company's automated information system that uses blockchain technology.